EXPLORING AUDIOVISUAL DISSONANCE IN PRACTICE-BASED FILMMAKING: REPRESENTING DILEMMA IN BENDERA PUTIH - Utami, Citra Dewi; Arifianto, Budi Dwi (ISI Press Institut Seni Indonesia Surakarta, 2025)
Bendera Putih (2023), a short fiction film that strategically employs audiovisual dissonance to represent a profound dilemma, was produced in Yogyakarta as part of a community-based film initiative funded by the Yogyakarta City Cultural Service's Special Fund and was officially screened at the 2024 JAFF. Adopting a practice-based approach, this study investigates how the deliberate juxtaposition of visual and auditory elements crafts narrative ambiguity and intense emotional tension. Drawing on theories of cinematic dissonance, narrative disruption, and experiential learning, the article reflects on how asynchronous audio-visual pairings challenge audience expectations and provoke complex ethical and moral reflections. The socio-cultural context of the Yogyakarta community, known for upholding the value of